1981
DOI: 10.1152/jappl.1981.51.6.1484
|View full text |Cite
|
Sign up to set email alerts
|

Vagotomy reverses apnea induced by high-frequency oscillatory ventilation

Abstract: Apnea has been observed in both animals and patients during high-frequency oscillatory ventilation. The effects of vagotomy were studied during periods of oscillator-induced apnea in 11 pentobarbital-anesthetized dogs. The animals were intubated and breathing spontaneously. An arterial cannula was inserted for monitoring blood pressure and blood gases. Intratracheal airway pressure was measured, and respiratory activity was assessed using either an intrapleural catheter or esophageal balloon. The dogs then und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

1983
1983
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…Therefore, reflex effects of both SAR and RAR stimulation may occur during HFO. Although the most often reported effect of HFO on respiration is SAR-mediated inhibition of spontaneous breathing, expressed as prolonged expiration, the maximum response being apnea [2][3][4]24], RAR-mediated excitatory effects expressed by induction of tonic diaphragmatic activity, increase of breathing frequency, and elicitation of augmented breaths were also observed during HFO [5,[8][9][10]25]. The resulting respiratory response to HFO depends obviously on the balance between SAR and RAR activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reflex effects of both SAR and RAR stimulation may occur during HFO. Although the most often reported effect of HFO on respiration is SAR-mediated inhibition of spontaneous breathing, expressed as prolonged expiration, the maximum response being apnea [2][3][4]24], RAR-mediated excitatory effects expressed by induction of tonic diaphragmatic activity, increase of breathing frequency, and elicitation of augmented breaths were also observed during HFO [5,[8][9][10]25]. The resulting respiratory response to HFO depends obviously on the balance between SAR and RAR activity.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency oscillation ventilation (HFO) has been shown to induce a normocapnic vagally mediated apnea [24], and subsequent findings confirmed the Offprint requests to: Jana Kohl effect of vagal nerves in mediating other respiratory responses to HFO, such as lengthening of expiration, induction of tonic diaphragmatic activity, increase of breathing frequency, and elicitation of augmented breaths [2,3,5,8,25]. Therefore, information about vagal afferent activity during HFO was considered essential to understand the mechanisms underlying the effects of HFO on breathing control.…”
Section: Introductionmentioning
confidence: 99%
“…The apnoea produced by HFV has been attributed to causes other than pulmonary receptor activity. A lower Pa,co during HFV certainly promotes apnoea (Zwart, Jansen & Versprille, 1981) and it has been suggested that extravagal afferents are involved (Butler et al 1980;Thompson et al 1980). However, the speed of onset of apnoea and its abolition by vagotomy in the present and previous experiments (Kohl & Koller, 1984;Banzett, Reid & Lehir, 1985) demonstrate these factors are not essential for its production.…”
Section: Discussionmentioning
confidence: 99%
“…Carlon, Ray, Klain & McCormack, 1980). A striking characteristic of HFV is its ability to produce apnoea which is not the result of hypocapnia (Butler, Bohn, Bryan & Froese, 1980;Thompson, Marchak, Bryan & Froese, 1980). This apnoea has been attributed to the increased activity of slowly adapting pulmonary stretch receptors (PSRs) in response to HFV (Wozniak, Davenport & Kosch, 1983), and by Sant' Ambrogio & Davenport (1986) in response to high-frequency oscillations of the tracheal wall.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable confusion in the literature as to whether HFV per se causes inhibition of spontaneous ventilation [8,16,17,28,32,57]. Such an effect is seen in experimental animals and in human infants, but not in adult humans, at least as regards HFJV.…”
Section: Control Of Breathingmentioning
confidence: 99%